Planning for town centre revitalisation in a declining context : a thesis presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning at Massey University, Palmerston North, New Zealand - Gram, Lauren (Massey University, 2017)
"This research explored how the Ruapehu District views its declining population and economy, how town centre revitalisation has attempted to address decline in Ohakune, and the outcomes of this revitalisation, with the aim of developing guidelines for local authorities in declining contexts to consider when undertaking revitalisation to address decline. As the Ruapehu District Council is including town centre renewal as part of their aspirations for economic development and reversing decline, this research looks at the effects of revitalisation of town centres in a declining context by asking the question: What should local authorities in declining contexts consider when planning for town centres to enable people and communities to provide for their social, economic, cultural and environmental well-being?"--Research Aim & Question, p. 7
Keywords: Urban renewal; Ohakune; New Zealand